Like a river glorious - Carson, Rae 1973- (Carson, Rae Gold seer trilogy)
Having arrived in California, Lee Westfall's magical power is growing and changing every day and may be enough, with help from her true friends, to stop her villainous Uncle Hiram when he kidnaps her and sends her deep into his gold mine